(untitled) (Zoological Records and Reviews, 2023)
Forest degradation – the partial loss of forest structure, composition, and ecological function without complete conversion – affects far greater areas of tropical forest than outright deforestation, yet its consequences for animal biodiversity are less thoroughly documented. Degraded forests retain some structural complexity and species, but selective logging, fuelwood extraction, grazing, and repeated fire alter canopy cover, understorey structure, and species composition in ways that differentially affect animal communities across taxonomic groups and functional guilds. This study presents a comprehensive assessment of animal diversity across a forest degradation gradient in the Eastern Ghats of Andhra Pradesh, comparing intact forest, lightly degraded forest, moderately degraded forest, and heavily degraded scrub at 48 sites surveyed using standardised camera trapping, bird point counts, herpetofauna VES, and invertebrate sampling over two years (2021-2023). A total of 384 animal species from five groups are documented. All groups showed significant species richness declines with degradation intensity, but at different rates: large mammals declined most steeply (-72.4% from intact to heavily degraded), while generalist birds showed the smallest decline (-18.4%). Canopy cover, understorey structural complexity, and distance from nearest intact forest are the three strongest predictors of animal diversity. Recovery trajectories under active restoration are assessed. Management recommendations for biodiversity-sensitive forest management and restoration are presented.